Gaya Kata dalam Kumpulan Puisi Doa Untuk Anak Cucu Karya W.S. Rendra dan Implementasinya sebagai Bahan Ajar Sastra di SMA (Kajian Stilistika) - Safitri, Nova; , Prof. Dr. Ali Imron Al-Ma'ruf, M.Hum (2017)
This study aims to (1) To describe the background sosiohistoris W.S. Rendra, (2) describe the style of words contained in a collection of poems Doa untuk Anak Cucu by W.S. Rendra, (3) describe the meaning of style words are contained in a collection of poems Doa untuk Anak Cucu by W.S. Rendra terms of stilistika, and (4) Describe the implementation of research results in the word style of poetry Doa untuk Anak Cucu by W.S. Rendra as teaching materials Indonesian Literature for Elementary High School. Data collection techniques in this study are techniques of literature and other sources such as previous relevant research and theories concerning the assessment stilistika. Data analysis techniques in this study using a model of semiotic readings among reading heuristic and hermeneutic reading. The validity of the data in this study using the technique of triangulation theory. The results of this study, namely (1) Willybrordus Surendra Bhawana or Rendra Rendra Brotoatmojo is the full name. Rendra works include a collection of poems, short stories, and drama also its has been translated into many foreign languages. Start working for literature've seen in junior high school. Characteristic authorship theme of W.S. Rendra are social criticism, injustice, oppression of poor people, education, and love. (2) Style words contained in a collection of poems Doa untuk Anak Cucu by W.S. Rendra includes connotative words, concrete words, a loan word from a foreign language, said a typical greeting or name themselves, the word with the object of the reality of nature, vulgar words and vocabulary Java. (3) Making of style words are contained in a collection of poems Doa untuk Anak Cucu by W.S. Rendra there are two dimensions, first Dimensions of religiosity of the human relationship with God and second is the social dimension of the welfare of the people were restrained by officers and employees. (4) Implementation of research results in accordance with the standards of competence 14. Expressing opinion on poetry through discussion. 14.1 discusses basic competence with respect to a picture poem sensing, feeling, mind, and imagination through discussion.